2022
DOI: 10.3389/fmicb.2022.991703
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility and molecular characteristics of Cryptococcus spp. based on whole-genome sequencing in Zhejiang Province, China

Abstract: Cryptococcus spp. is a complex species that often causes cryptococcosis, which is one of the most common opportunistic infections in adults living with HIV and has very high morbidity and mortality rates. This study aimed to investigate the antifungal susceptibility profiles and epidemiological characteristics of the Cryptococcus neoformans species complex (CNSC) and the Cryptococcus gattii species complex (CGSC) in Zhejiang Province, China. A total of 177 CNSC and 3 CGSC isolates were collected, and antifunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Similarly, strains with 5-fluorocytosine and fluconazole MIC >16 μg/mL have also been reported in other Asian countries, such as Thailand, India and Indonesia ( Khayhan et al, 2013 ). To date, the rate of resistance to amphotericin B ranges from 1 to 75% ( Li et al, 2020 ; Zhang et al, 2022 ; Zhou et al, 2022 ). While there is no apparent upward trend in the annual increase of antifungal resistance among Cryptococcus strains in the Guangdong region, a substantial proportion of isolates do exhibit MIC values near the clinical breakpoints, particularly against amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, strains with 5-fluorocytosine and fluconazole MIC >16 μg/mL have also been reported in other Asian countries, such as Thailand, India and Indonesia ( Khayhan et al, 2013 ). To date, the rate of resistance to amphotericin B ranges from 1 to 75% ( Li et al, 2020 ; Zhang et al, 2022 ; Zhou et al, 2022 ). While there is no apparent upward trend in the annual increase of antifungal resistance among Cryptococcus strains in the Guangdong region, a substantial proportion of isolates do exhibit MIC values near the clinical breakpoints, particularly against amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive analysis in the context of clinical use and prognosis in the region should be carefully performed. In addition, studies have also found that the emergence of drug-resistant strains could be associated with gene mutations ( Li et al, 2020 ; Zhang et al, 2022 ; Zhou et al, 2022 ). Notably, although itraconazole, voriconazole and posaconazole are not recommended as the first choice by the guidelines for the treatment of cryptococcosis, clinical strains in the region maintain a low MIC ( Table 2 ), which was consistent with the findings from other studies ( Khayhan et al, 2013 ; Fan et al, 2016 ) that indicated that itraconazole, voriconazole and posaconazole can be used as alternatives when the strains isolated from patients became resistant to first-line agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, positive outcomes have been reported with fungal biocontrol agents (BCAs) such as Cryptococcus spp. (Zhang et al ., 2022), Trichoderma (Mondani et al ., 2021), Simplicillium (Abaya et al ., 2021), Clonostachys spp. (Abdellatif et al ., 2022), and various other species (Comby et al ., 2017; Rojas et al ., 2020; Hao et al ., 2021; Noel et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%